Design and experimental research on disc-type seeding device for single-bud sugarcane seeds - Liu, Xinpeng; Niu, Zhaojun; Li, Ming; Hou, Mingxin; Wei, Lijiao; Zhang, Yuan; Huang, Li (International Journal of Agricultural and Biological Engineering, 2023)
Mechanized sugarcane seeding is one of the effective technical measures for improving seeding uniformity and operation efficiency. However, the imperfection of supporting equipment limits the promotion and application of this technology. As there are some problems in domestic sugarcane planting machines currently, such as large auxiliary labor, high labor intensity, low seeding uniformity, and large amount of seeds, a disc-type single-bud sugarcane seed metering device was innovatively designed on the basis of the analysis of physical properties of single-bud sugarcane seeds and the combination with agronomic requirements for field planting in this paper. Solidworks was used to simulate and analyze the mechanism, check the theoretical parameters, and process the test prototype. Through single-factor experiments, the effective factors affecting seeding uniformity were determined. A multi-factor orthogonal rotation test was designed, data were collected and then SPSS was used to get the optimal parameters for the seeding uniformity: the advancement speed of machine is 0.22 m/s, the number of disc seeding grooves is 10, the rotating disc speed is 0.18 r/s, and the seeding uniformity is 86.2%; the seeding uniformity was verified by field trial, and the results showed that the average seeding uniformity of the field verification was 83%, with the error 3.2% relative to the optimization result. The relative error is within 10%, indicating that the optimization result is reliable and meets the requirements of seeding uniformity, thus providing theoretical basis for the research and development of the disc-type single-bud seeding device.Key words: sugarcane, single-bud sugarcane seed, disc-type seeding device, seeding uniformityDOI: 10.25165/j.ijabe.20231602.6973Citation: Liu X P, Niu Z J, Li M, Hou M X,Wei L J, Zhang Y, Huang L. Design and experimental research on disc-type seeding device for single-bud sugarcane seeds. Int J Agric & Biol Eng, 2023; 16(2): 115－124.